Analisis Faktor-faktor yang Mempengaruhi Kebertahanan Pedagang Kuliner Tradisional di Kabupaten Klungkung - Mustika, Made Dwi Setiadhi; Apriliani, Putu Desy (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143))
Community empowerment based on local wisdom is needed in order to sustain poverty reduction policies. Developing economic based on local wisdom in addition to increasing revenue and consumption. This research was aimed to analyze the factors that influence the viability of traditional culinary serombotan traders, in an effort to preserve local wisdom in Klungkung regency, as well as to look at the characteristics of the serombotan traders in Klungkung regency. The results of the analysis of the characteristics of traders shows that of the total 50 samples, most serombotan traders are in the age range 26-35 years. Meanwhile, the results of factor analysis showed that the viability of traditional culinary serombotan traders in Klungkung regency is influenced by two main factors, namely the External Factors (Marketing Process and Presence Influence Competitor) and Internal Factors (Ease of Obtaining Venture Capital, Raw Material Availability and Processing Raw Materials). The five factors are incorporated into these two major factors affecting the viability of 66.022 percent serombotan traders. The remaining 33.978 percent is influenced by other factors which not included in the analysis.
Keywords: Traditional Culinary , Viability Analysis , Factor Analysis